2004
DOI: 10.1200/jco.2004.07.131
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mobilization of CD34+ Cells Following Administration of the CXCR4 Antagonist AMD3100 to Patients With Multiple Myeloma and Non-Hodgkin's Lymphoma

Abstract: AMD3100 appears to be a safe and effective agent for the rapid mobilization of CD34+ cells in patients who have received prior chemotherapy. Further studies in combination with granulocyte colony-stimulating factor in patients with lymphoid malignancies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
266
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(278 citation statements)
references
References 53 publications
4
266
0
8
Order By: Relevance
“…The general feasibility and safety of such an approach has been demonstrated by recent studies in which CXCR4 antagonists were administered to patients or volunteers. 24,40,41 Stroma-mediated AML cell protection from chemotherapy can partially be reversed by CXCR4 antagonists in vitro. 42 As such, a clinical trial with administration of a CXCR4 antagonist in an attempt to mobilize AML cells from their protective environment prior to conventional therapy may be feasible in the near future, even though an increased toxicity to normal hematopoiesis due to simultaneous progenitor cell mobilization is a concern.…”
Section: Discussionmentioning
confidence: 99%
“…The general feasibility and safety of such an approach has been demonstrated by recent studies in which CXCR4 antagonists were administered to patients or volunteers. 24,40,41 Stroma-mediated AML cell protection from chemotherapy can partially be reversed by CXCR4 antagonists in vitro. 42 As such, a clinical trial with administration of a CXCR4 antagonist in an attempt to mobilize AML cells from their protective environment prior to conventional therapy may be feasible in the near future, even though an increased toxicity to normal hematopoiesis due to simultaneous progenitor cell mobilization is a concern.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, AnorMED explored AMD3100 as a mobilizing agent for HSC, 88 and a subsequent series of preclinical and clinical trials demonstrated that AMD3100 alone and in combination with G-CSF mobilizes HSC. 34,89,90 AMD3100 (recently re-named as Plerixafor or Mozobil) is now owned by Genzyme Corporation (Cambridge, MA, USA) after a recent takeover of AnorMED by Genzyme in late 2006. Plerixafor is currently used in phase III trials in lymphoma and multiple myeloma patients undergoing autologous stem cell mobilization, and current plans are to file for US and European approval of the drug in 2008.…”
Section: Non-peptide Cxcr4 Antagonistsmentioning
confidence: 99%
“…Significant enhancement of PBSC mobilization was shown. [20][21][22][23][24][25][26] We evaluated the results of combined use of plerixafor and G-CSF in 20 patients who had previously failed to mobilize sufficient PBSCs, to allow the patients to proceed to auto-SCT, after obtaining consent for compassionate use of the experimental agent. Of the 20 patients, 5 had failed previous chemotherapy-based PBSC mobilization and 15 failed previous cytokine-only mobilization.…”
Section: Introductionmentioning
confidence: 99%